The THE EFFECT OF TAX INCENTIVES, TAX RATES AND TAX SANCTIONS ON TAX COMPLIANCE WITH TAX SERVICES IN THE COVID-19 PANDEMIC AS A MODERATION VARIABLE - Faiz, Ahmad (Accounting Department UNUSIA, 2024)
In this study, the mixed method was used with a non-probability sampling technique - a purposive sample aimed at 200 respondents who are domiciled in the DKI Jakarta area and interviewing tax employee informants. In the results of this study found the results of the analysis in the form of tax incentives have a positive effect on tax compliance, tax rates have a positive effect on tax compliance, tax sanctions have a positive effect on tax compliance, tax incentives cannot strengthen the relationship between tax services and tax compliance, tax rates can strengthen service relationships taxes with tax compliance and tax sanctions can strengthen the relationship between tax services and tax compliance. The data is relevant from respondents who are aligned with the informants.